PENERAPAN LATIHAN LARI SPRINT 50 METER UNTUK MENINGKATKAN KEMAMPUAN SISWA MENGGIRING BOLA DALAM PERMAINAN SEPAK BOLA - Badri, Syamsul (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to improve students' ability to dribble by doing sprint running exercises, with this exercise the researchers hope that the speed of students in playing ball while carrying the ball will increase, the research conducted was classroom action research which was carried out in two cycles, namely in cycle 1 the lowest score is 64, the highest score is 80 and the average grade is 72.2 with sufficient category. this can be shown by classical completeness of classical completeness of 80%, and after the second cycle the results obtained are very satisfactory, namely increasing with the lowest value of 75, the highest value of 80 with an average value of 78.2 classical completeness to 100%. In this study, it was seen that with the 50-meter sprint practice the students' ability to dribble the ball better, this also increases the students' ability to play ball.